The Mission of Demythologizing : Rudolf Bultmann's Dialectical Theology - Congdon, David W. (Book collections on Project MUSE., 2015)
Since 1941, Rudolf Bultmann's program of demythologizing has been the subject of constant debate, widely held to indicate Bultmann's departure from the dialectical theology he once shared with Karl Barth. In the 1950s, Barth referred to their relationship as that of a whale and an elephant: incapable of meaningful communication. This study proposes a contrary reading of demythologizing as the hermeneutical fulfillment of dialectical theology on the basis of a reinterpretation of Barth's theological project. As such, the volume argues that dialectical theology is fundamentally governed by a missionary logic. Bultmann's hermeneutical theology extends this dialectical, missionary theology into the field of interpretation. Contrary to many critics, the message of God's saving work in Christ, and not modern science, funds Bultmann's hermeneutical program. Like Barth's own revolution, Bultmann's program addresses a false relation between gospel and culture. Negatively, demythologizing is a program of deconstantinizing, opposing the objectifying conflation of kerygma and culture that he calls "myth." Positively, demythologizing is a form of intercultural hermeneutics, composed of preunderstanding and self-understanding. Demythologizing is therefore a missionary hermeneutic of intercultural translation.